2012
DOI: 10.1097/mao.0b013e31825d644a
|View full text |Cite
|
Sign up to set email alerts
|

Auditory and Vestibular Symptoms and Chronic Subjective Dizziness in Patients With Ménière’s Disease, Vestibular Migraine, and Ménière’s Disease With Concomitant Vestibular Migraine

Abstract: Comorbidity was common between MD and VM, and their symptoms overlapped. More specific diagnostic criteria are needed to differentiate these diseases and address their coexistence. CSD co-occurred with VM but was rarely seen with MD.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
158
1
12

Year Published

2014
2014
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 185 publications
(179 citation statements)
references
References 42 publications
(39 reference statements)
8
158
1
12
Order By: Relevance
“…This feature is a "must-have feature" in this type of questionnaire [5,[33][34][35] . Demographic features, familial MD history, accompanying other systemic chronic disease history, and bilaterality of the disease findings were similar to those of other studies [36][37][38][39][40][41] . It has been reported that the emotional stress is the most powerful attack indicator [31,[41][42][43][44] .…”
Section: Discussionsupporting
confidence: 76%
See 1 more Smart Citation
“…This feature is a "must-have feature" in this type of questionnaire [5,[33][34][35] . Demographic features, familial MD history, accompanying other systemic chronic disease history, and bilaterality of the disease findings were similar to those of other studies [36][37][38][39][40][41] . It has been reported that the emotional stress is the most powerful attack indicator [31,[41][42][43][44] .…”
Section: Discussionsupporting
confidence: 76%
“…Our finding was the same. Moreover, the audiological, eye movement, and bithermal caloric test findings of the patients were similar to the literature [19,35,[37][38][39][45][46][47][48][49][50][51][52] . Head-shaking nystagmus has been reported as 60% previously, though the value was 20.4% in this study [38] .…”
Section: Discussionsupporting
confidence: 69%
“…The 14-item Hospital Anxiety and Depression Scale (HADS) covers both anxiety and depressive symptoms [102]. Positive results indicate that an anxiety or depressive disorder is likely, either as the sole cause of vestibular symptoms or co-existing with PPPD [12,58,75,79]. As described in Note 5, patients may avoid circumstances that exacerbate PPPD because of the noxious nature of persistent vestibular symptoms.…”
Section: Chronic Anxiety and Depressive Disordersmentioning
confidence: 99%
“…When PPPD co-exists with these disorders, proper diagnosis rest on identifying the characteristic symptoms of each active disorder. Episodic disorders add distinctive vestibular symptoms to the background of PPPD [58], such acute attacks of vertigo plus cephalalgia, photophobia and phonophobia, with or without visual aura for vestibular migraine [49], short-lived positional vertigo for BPPV [87], or attacks of vertigo, tinnitus, and fluctuating hearing for Menière's disease [51].…”
Section: Recurrent Attacks Of Episodic Precipitantsmentioning
confidence: 99%
“…Привлекает внимание высокая частота выявления ГЛ у пациентов с МБТ: причинно-следственная связь не оче-видна [9][10][11]. Клинические проявления заболеваний имеют много общего, сохраняя и существенные различия (табл.…”
Section: результаты и обсуждениеunclassified